Headmasters' Effectiveness in Making Decisions through an Emotional Intelligence Approach - Sowiyah Sowiyah (Universitas Negeri Malang, 2016)
Headmasters as leaders are responsible for the advancement of the organization of their schools. To commit their duties, they deal with more human than technical aspects. They have to use an emotional approach to making rapports with their subordinates in order to cooperate with them productively and emotionally. Effective competencies the headmasters should possess are building ties, collaboration and cooperation, and team ability. The team members should also make a cooperation through a healthy interaction, the interaction which enables them to make an in-debth, open debate, tested against others' critical opinions. They keywords in such a successful interaction is an emotional intelligence such as self-intelligence, empathy, and communication.